More Than Barriers: Institutional Misalignments and The Flawed Implementation of Farmer Corporation in Indonesia - Rahman, Mizan Ikhlasul; Wisnu Putra Danarto; Rosalina Kumalawati (Jurnal AGRISEP, 2026)
Effective institutional arrangements and policies can transform the agricultural sector by enhancing productivity to address present and future challenges. The food estate based on farmer corporation is viewed as a promising model for agricultural institutional development. It has the potential to integrate various agricultural activities from upstream to downstream, thereby increasing farmers’ overall productivity and welfare. However, institutional misalignments hinder optimal outcomes. This study employs a blended approach that includes an exploratory study and a deductive thematic analysis guided by the Institutional Analysis and Development (IAD) framework. The exploratory study emphasizes the importance of developing agricultural institutions and identifies key gaps between the grand design of food estate and its actual implementation. Meanwhile, the deductive thematic analysis further explores stakeholders’ perspectives, serving as a foundation for the analysis using the IAD framework. The study finds that ineffective implementation of the food estate and the suboptimal establishment of farmer corporation are caused by stakeholders’ limited understanding, weak coordination, insufficient technology, low skills and capacities among human resources, and limited access to capital. Additionally, when developing agricultural institutions, it is essential to consider the local community’s support and trust to improve the suitability of the selected institutional form. Furthermore, agricultural institutional development should be supported by a well-organized structure, clear operational plans, and core activities to ensure sustainable implementation.